2019
DOI: 10.21203/rs.2.12236/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Transcription Factors related to Diabetic Tubulointerstitial Injury

Abstract: Background: Diabetic nephropathy (DN) is a main cause of chronic renal failure. Despite decades of extensive study, the molecular mechanisms underlying diabetic tubulointerstitial injury remain unclear. We aim to identify key transcription factor genes involved in diabetic tubulointerstitial injury. Methods: A microarray dataset (GSE30122) from Gene Expression Omnibus (GEO) was downloaded. A total of 38 transcription factor genes based on 166 differentially expressed genes(DEGs) were identified by UCSC_TFBS. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Enrichment analysis indicated that these genes are signi cantly overrepresented in pathways such as PI3K-Akt signaling, ECM-receptor interaction, AGE-RAGE signaling in diabetic complications, the Renin-angiotensin system, and the Complement and coagulation cascades. These pathways are intimately related to the pathological alterations observed in DN, corroborating ndings from preceding research [38,39].…”
Section: Discussionsupporting
confidence: 91%
“…Enrichment analysis indicated that these genes are signi cantly overrepresented in pathways such as PI3K-Akt signaling, ECM-receptor interaction, AGE-RAGE signaling in diabetic complications, the Renin-angiotensin system, and the Complement and coagulation cascades. These pathways are intimately related to the pathological alterations observed in DN, corroborating ndings from preceding research [38,39].…”
Section: Discussionsupporting
confidence: 91%
“…EPHA3 has been proven to play an important role in cancer 25 and energy metabolism, 26 and it might participate in the currency of OA 27 . The expression of CEBPB decreased in patients with DN, 28 and the overexpression of CEBPB could reverse the proliferation of OA‐FLS cells induced by hypoxia 29 . UBAP1 played an important role in NF‐kB signal transduction 30 .…”
Section: Discussionmentioning
confidence: 99%
“…However, despite advancements in treatment options [1,3,4], effective prevention and management of DKD remain limited, and reliable biomarkers to predict disease progression are lacking. Although recent research has mainly concentrated on glomerular diseases, emerging evidence indicates that tubulointerstitial injury may independently contribute to renal disease progression [5,6]. More importantly, tubular damage mediated by inflammation seems to predominate over glomerular injury in early DKD [7].…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics approaches have been increasingly utilized to identify differentially expressed genes (DEGs) from gene microarrays and high-throughput sequencing data. Recent efforts [6,16] have identified DEGs associated with tubulointerstitial injury in DKD, potentially obtaining a novel, effective approach to elucidate the pathogenic mechanisms of DKD and uncover new therapeutic targets. This study is aimed at comprehensively analyzing the association between NET-related genes (NRGs) [17] and the DEGs to discern DKD patients effectively.…”
Section: Introductionmentioning
confidence: 99%